2013
DOI: 10.1073/pnas.1216336110
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila ORB protein in two mushroom body output neurons is necessary for long-term memory formation

Abstract: Memory is initially labile and gradually consolidated over time through new protein synthesis into a long-lasting stable form. Studies of odor-shock associative learning in Drosophila have established the mushroom body (MB) as a key brain structure involved in olfactory long-term memory (LTM) formation. Exactly how early neural activity encoded in thousands of MB neurons is consolidated into protein-synthesis-dependent LTM remains unclear. Here, several independent lines of evidence indicate that changes in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
147
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(159 citation statements)
references
References 44 publications
10
147
2
Order By: Relevance
“…Existing expression data suggest that the localization of Orb and Orb2 does not overlap substantially, and they may in fact down-regulate the expression of the respective paralogue (13,19). Indeed, both Orb and Orb2 are involved in LTM, albeit in distinct neuronal classes (12,15). A mechanism of acquiring functional divergence in which changes in protein expression patterns are faster than changes in target sequence specificity was suggested for DNA-binding proteins and constitutes a likely pattern in the evolution of nucleic acid-binding protein families (58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing expression data suggest that the localization of Orb and Orb2 does not overlap substantially, and they may in fact down-regulate the expression of the respective paralogue (13,19). Indeed, both Orb and Orb2 are involved in LTM, albeit in distinct neuronal classes (12,15). A mechanism of acquiring functional divergence in which changes in protein expression patterns are faster than changes in target sequence specificity was suggested for DNA-binding proteins and constitutes a likely pattern in the evolution of nucleic acid-binding protein families (58).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular machinery controlling local protein synthesis has been best studied in vertebrate oocyte development during which members of the cytoplasmic polyadenylation element binding (CPEB) protein family, in concert with other RNA-binding proteins, control the temporal expression of maternal RNAs (8,9). More recently, CPEB proteins also have been found to be expressed in adult nervous systems (10)(11)(12)(13) where they are thought to be involved in synaptic plasticity and LTM (12,(14)(15)(16)(17), suggesting evolutionary conservation of the mechanism of local translation across species, tissues, and developmental stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MB α/β subdivisions might communicate with each other through feedback loops constructed by various MB extrinsic neurons, such as DPM neurons and APL neurons (Lee et al, 1999;Keene et al, 2006;Wu et al, 2011;Pitman et al, 2011). Another possibility is that MB α/β subdivisions, being parallel with each other, release neurotransmitters to their common downstream neurons suggested for LTM storage, such as the DAL neurons (Chen et al, 2012) MB-V2 neurons (Séjourné et al, 2011), MB-V3 neurons (Pai et al, 2013) and the ellipsoid body (Wu et al, 2007), to regulate formation, consolidation and retrieval of LTM separately.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown pattern sensitivity of different molecular processes relevant for these events (Ye et al 2008;Akalal et al 2010;Kim et al 2010;Pai et al 2013). Wu et al (2001) showed that spaced depolarizationinduced activation of extracellular signal-regulated kinase (ERK) is longer lasting than the ERK activation induced by massed pattern of stimulation.…”
mentioning
confidence: 99%